Chlorogenic Acid‐Conjugated Nanoparticles Suppression of Platelet Activation and Disruption to Tumor Vascular Barriers for Enhancing Drug Penetration in Tumor. Issue 9 (25th December 2022) - Ke, Yue; Ma, Zhifang; Ye, Hongbo; Guan, Xinghua; Xiang, Zehong; Xia, Yu; Shi, Qiang
Abstract: Hypercoagulation threatens the lives of cancer patients and cancer progression. Platelet overactivation attributes to the tumor‐associated hypercoagulation and maintenance of the tumor endothelial integrity, leading to limited intratumoral perfusion of nanoagents into solid tumors in spite of the enhanced penetration and retention effect (EPR). Therefore, the clinical application of nanotherapeutics in solid cancer still faces great challenges. Herein, this work establishes platelet inhibiting nanoagents based on Fe III ‐doped C3 N4 coloaded with the chemotherapy drug and the antiplatelet drug chlorogenic acid (CA), further opening tumor vascular endothelial junctions, thereby disrupting the tumor vascular endothelial integrity, and enhancing drug perfusion. Moreover, CA not only damages the cancer cells but also potentiates the cytotoxicity induced by the chemotherapy drug doxorubicin, synergistically ablating the tumor tissue. Further, the introduction of CA relieves the original causes of the hypercoagulable state such as tissue factor (TF), thrombin, and matrix metalloproteinases (MMPs) secreted by cancer cells. It is anticipated that the hypercoagulation‐ and platelet‐inhibition strategy by integration of phenolic acid CA into chemotherapy provides insights into platelet inhibition‐assisted theranostics based on nanomedicines. Abstract : Antiplatelet activation synergistic chemotherapy scheme is formed through the introduction of antiplatelet drug chlorogenic acid (CA). Once activated platelets are inhibited, the level of tumor‐secreted procoagulant factors is downregulated, the hypercoagulability of tumor blood environment is fundamentally relieved, and the switch of tumor vascular barrier is "turned on, " which enhances drug leakage and significantly improves cancer chemotherapy.